0603 Changes in Healthcare Visits and Exercise habits Associated with Poor Sleep in Sleep Medicine Patients during the COVID-19 Pandemic. (25th May 2022) - Kokonda, Manasa; Debian, Ahmad; Arentson-Lantz, Emily; Shaib, Fidaa; Nowakowski, Sara
Abstract: Introduction: Patients may be experiencing increased stress and sleep disturbance due to healthcare and changes in daily habit during the COVID-19 pandemic. Healthcare changes may include telemedicine visits, delayed or canceled appointments and sleep studies. The purpose of this study was to assess the association between changes in healthcare and daily habits on sleep. Methods: Sleep medicine clinic patients completed an online survey during the pandemic and again 6 months later (December 2020 - May 2021), where they answered questions about COVID-19 (COVID-19 vaccination and test results, changes in health care visits and habits during the pandemic), PROMIS measures (Sleep Disturbance, Sleep-Related Impairments), and Insomnia Severity Index (ISI). General linear regression model was performed using SAS to determine if changes in healthcare and daily habits predicted poorer sleep. Results: Among 81 patients who completed baseline survey, 54 (aged 55.2±18.4 y, 61% female, 70% Caucasian) completed the 6-month follow-up survey. Among them, 6% tested positive for COVID-19 and 83% were vaccinated. 30% changed their healthcare office appointments to telephone visits, 50% changed to video visits; whereas 22% cancelled and 30% rescheduled their healthcare appointments. At baseline, changes in health care visits had significant increase on ISI (3.98 ± 1.66, p=0.02). Upon follow-up, changes in health care visits had significant increase on ISI (4.77 ± 2.12, p=0.03) and Sleep Impairments (7.97 ± 3.83, p=0.04). A decrease in exercise predicted lower Sleep Disturbance (6.81 ± 3.31, p=0.04). Conclusion: Sleep medicine patients who reported changes in health care visits at baseline and 6-month follow up reported higher insomnia severity, and sleep-related impairments. Changes in healthcare had deleterious effects on sleep and should be considered when managing patients' healthcare. Unexpectedly, patients who reported a reduced level of exercise reported improved sleep. Pandemic public policies (e.g., gym closures) may have made it more difficult to exercise but allowed for greater opportunity to sleep. Support (If Any): This work is supported by National Institutes of Health (NIH) Grant # R01NR018342 (PI: Nowakowski) and by the Department of Veteran Affairs, Veterans Health Administration, Office of Research and Development, and the Center for Innovations in Quality, Effectiveness and Safety (CIN 13-413).